Introduktion til studiet af de praksisser der ’driver staten’ - Nielsen, Niels Jul; Garnett, Izabella; Lehn, Maja; Kristensen, Marlene Paulin (Culture and History: Student Research Papers, 2024)
This introduction aims to situate this special issue’s explorations of the relationship between civil servants’ everyday practice and state reforms in contemporary Denmark. The introduction gives an overview of the Civil Servant analytics, developed within the framework of the ethnological State and Life-Mode Analysis. The Civil Servant analytic offers a method for studying the relationship between state management and civil servant practice, and does so by specifying three different, but interdependent dimensions of the civil servant practice, namely: policy-development, operationalization, and policy-implementation. Using the lens of the Civil Servant Life-mode, the articles in this special issue study the everyday strategies and rationales that civil servants apply while navigating between political reforms, professional convictions, and state interests in a context of a New Public Management and New Public Governance state paradigms.